1996
DOI: 10.1093/glycob/6.6.627
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase levels in guinea pig blood are increased after systemic infection with Aspergillus fumigatus

Abstract: The presence of chitinase activity in human serum has recently been described by us. On that occasion we speculated on the possible role of mammalian chitinases as a defense mechanism against chitin-containing pathogens. The results of the present study substantiate our hypothesis. We demonstrate and partially characterize the chitinase activities that are present in plasma of guinea pigs and in homogenates of A.fumigatus with the aid of the substrates MU-[GlcNAc]2,3 and also with glycol [3H]chitin. Upon infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
46
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 25 publications
7
46
0
4
Order By: Relevance
“…We subsequently showed that the enzyme was also present in guinea pig serum and in rat liver (Overdijk et al, 1996a;Overdijk & Van Steijn, 1994). Subcellular fractionation studies with rat liver homogenates showed that the enzyme has a lysosomal localization.…”
Section: Introductionmentioning
confidence: 91%
“…We subsequently showed that the enzyme was also present in guinea pig serum and in rat liver (Overdijk et al, 1996a;Overdijk & Van Steijn, 1994). Subcellular fractionation studies with rat liver homogenates showed that the enzyme has a lysosomal localization.…”
Section: Introductionmentioning
confidence: 91%
“…Physiological and pathophysiological roles of bovine gut chitinase in blood are unknown. As Overdijk et al reported that the blood obtained from guinea pigs infected with Aspergillus fumigatus showed a higher chitinase activity than that of the control [13,14], we assumed that the bovine gut chitinase in the blood might play some defensive role against pathogens rather than act as a digestive enzyme. To test this hypothesis, we here established a semi-quantitative method for the measurement of bovine gut chitinase and investigated its changes with aging, systemic inflammation caused by lipopolysaccharide (LPS) injection, and experimental infection with Theileria sergenti in calves or cows.…”
mentioning
confidence: 91%
“…There are some reports showing the existence of chitinase activities in the sera of the goat, guinea pig, and human [10,[12][13][14]. By use of the present immunoblotting, we also tested the possibility that the antibody against bovine gut chitinase could detect protein bands in the plasma of other animal species (Fig.…”
mentioning
confidence: 94%
“…It was reported increased plasma ChT activity in neonates with fungal infection [10]. In a study made by Overdjik et al [23] Increased levels of chitinases have been reported in experimental Aspergillus fumigates infection. Neutrophils and monocytes/ macrophages play pivotal role in the defense mechanism against fungi, including cutaneous mycoses [24].…”
Section: Discussionmentioning
confidence: 97%